D1FHS, the Type Strain of the Ammonia-Oxidizing Bacterium Nitrosococcus wardiae spec. nov.: Enrichment, Isolation, Phylogenetic, and Growth Physiological Characterization - Wang, Lin; Lim, Chee Kent; Dang, Hongyue; Hanson, Thomas E.; Klotz, Martin G. (Frontiers in Microbiology, 2016)
An ammonia-oxidizing bacterium, strain D1FHS, was enriched into pure culture from a sediment sample retrieved in Jiaozhou Bay, a hyper-eutrophic semi-closed water body hosting the metropolitan area of Qingdao, China. Based on initial 16S rRNA gene sequence analysis, strain D1FHS was classified in the genus Nitrosococcus, family Chromatiaceae, order Chromatiales, class Gammaproteobacteria; the 16S rRNA gene sequence with highest level of identity to that of D1FHS was obtained from Nitrosococcus halophilus Nc4T. The average nucleotide identity between the genomes of strain D1FHS and Nitrosococcus halophilus strain Nc4 is 89.5%. Known species in the genus Nitrosococcus are obligate aerobic chemolithotrophic ammonia-oxidizing bacteria adapted to and restricted to marine environments. The optimum growth (maximum nitrite production) conditions for D1FHS in a minimal salts medium are: 50 mM ammonium and 700 mM NaCl at pH of 7.5 to 8.0 and at 37°C in dark. Because pertinent conditions for other studied Nitrosococcus spp. are 100-200 mM ammonium and <700 mM NaCl at pH of 7.5 to 8.0 and at 28-32°C, D1FHS is physiologically distinct from other Nitrosococcus spp. in terms of substrate, salt and thermal tolerance.